Aetiology and incidence of sudden cardiac arrest and death in young competitive athletes in the USA: a 4-year prospective study - Peterson, D. F.; Kucera, K.; Cox Thomas, L.; Maleszewski, J.; Siebert, D.; Lopez-Anderson, M.; Zigman, M.; Schattenkerk, J.; Harmon, K. G.; Drezner, J. A. (British Journal of Sports Medicine, 2021)
Objective: To investigate the aetiology and incidence of sudden cardiac arrest and death (SCA/D) in US competitive athletes.